2021
DOI: 10.1021/acs.nanolett.0c04468
|View full text |Cite
|
Sign up to set email alerts
|

Core Role of Hydrophobic Core of Polymeric Nanomicelle in Endosomal Escape of siRNA

Abstract: Efficient endosomal escape is the most essential but challenging issue for siRNA drug development. Herein, a series of quaternary ammonium-based amphiphilic triblock polymers harnessing an elaborately tailored pH-sensitive hydrophobic core were synthesized and screened. Upon incubating in an endosomal pH environment (pH 6.5–6.8), mPEG45-P­(DPA50-co-DMAEMA56)-PT53 (PDDT, the optimized polymer) nanomicelles (PDDT-Ms) and PDDT-Ms/siRNA polyplexes rapidly disassembled, leading to promoted cytosolic release of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 56 publications
1
48
0
Order By: Relevance
“…Increasing evidences demonstrated that only 3.5% (even less than 1%) internalized nucleic acid can escape from endosome and be released into the cytosol to mediate gene silencing [ [45] , [46] , [47] , [48] ], necessitating the development of delivery vehicles with the ability of rapid endosomal escape. Hence, we conducted the experiments to explore the endosomal escape of iLP181 and compare the advantages between iLP181 and commercial transfection reagents Lipo2000.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing evidences demonstrated that only 3.5% (even less than 1%) internalized nucleic acid can escape from endosome and be released into the cytosol to mediate gene silencing [ [45] , [46] , [47] , [48] ], necessitating the development of delivery vehicles with the ability of rapid endosomal escape. Hence, we conducted the experiments to explore the endosomal escape of iLP181 and compare the advantages between iLP181 and commercial transfection reagents Lipo2000.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the acid-cleavable ketal linkage in mPEG-b-P(HEMA-ketal-VB6) might increase the efficiency of the endosome escape. As Li et al identified, the hydrophobic core of a polyplex micelle results in the reduction of the endosome escape efficiency of the siRNA [ 42 ]. During internalization, the hydrophobic core of a polyplex micelle was suggested collapse [ 9 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…As Li et al identified, the hydrophobic core of a polyplex micelle results in the reduction of the endosome escape efficiency of the siRNA [ 42 ]. During internalization, the hydrophobic core of a polyplex micelle was suggested collapse [ 9 , 42 ]. In our study, the core of the polyplex could be destroyed upon the cleavage of the pyridoxal from the copolymer (as shown in Figure 3 c) at low pH.…”
Section: Resultsmentioning
confidence: 99%
“…At certain pH, these lipids are positively charged and thus feasible for the mRNA to interact electrostatically, and easily fused with cellular membrane [ 116 ]. After endocytosis, the ionizable cationic lipid becomes more positively charged due to proton-pump mediated pH reduction [ 117 ]. Once inside, the cationic lipids are removed by the endogenous anionic lipids and resulting in the release of mRNA in to the cytoplasm [ 118 ].…”
Section: Mrna Delivery Technologiesmentioning
confidence: 99%